Exploring outcomes of community-based tourism on the Kokoda Track, Papua New Guinea: a longitudinal study of Participatory Rural Appraisal techniques. Issue 8 (1st September 2016) - Reggers, Amy; Grabowski, Simone; Wearing, Stephen L; Chatterton, Paul; Schweinsberg, Stephen
ABSTRACT: The development of eco-trekking on the Kokoda Track, Papua New Guinea has used a community-based planning approach, Participatory Rural Appraisal (PRA), in developing community-based tourism (CBT). This approach involves local communities within the sustainable tourism planning process and honours and incorporates their knowledge and opinions. This paper examines the development and outcomes of CBT over a 10-year period since 2004. The findings suggest that stakeholder collaboration through the use of PRA and CBT can foster a sound capacity-building mechanism through the structures it creates as it provides a bottom-up approach which is enabling and meets the objectives of the stakeholders, particularly the communities that are engaged in the process. A key outcome of this process is a sustainable eco-trekking industry driven by the community, but working in partnership with tour operators and philanthropic giving. The paper also demonstrates the complexities, consequences and inevitable compromises in any outcome-based community approach which seeks to empower diverse stakeholder groups, and especially complex – and important – when working with indigenous peoples. The value of an effective, informed and relevant legal framework is noted, as is the need for the tapping into tour operators' experience as well as community experience.